I hate running and you can too : how to get started, keep going, and make sense of an irrational passion - Leonard, Brendan (Artisan Books, 2021)
"I Hate Running and You Can Too is a humorous, punchy, motivating guide to running longer distances than some might think sensible-whether that's a 5K or a marathon. Outside magazine columnist, chart-ist, and longtime runner, Brendan Leonard gets real on the love/hate relationship all runners have with the sport. He breaks down running in terms that speak to everyone who has ever struggled to get out the door and go for a run: getting comfortable being uncomfortable, how to start small and stick with it, that walking is a completely legitimate running strategy, and devising your own definition of success. Filled with 75 charts and graphs that give readers a sensible way to think about running, I Hate Running and You Can Too breaks down the reality of the training miles versus race miles, how to stay motivated, and what to do when faced with setbacks. I Hate Running and You Can Too shows readers that you won't always like running (sometimes you'll even hate it), but if you just keep going, you might learn to love it too"--